Utilization of NTT-Weave Waste for Pastors to Improve Community Economy in Kupang Regency - Koroh, Tince Dormalin; Fomeni, Melti Mehelina; Soinbala, Nusriwan Chrismanto; Kasse, Olivia (LP2M INSURI Ponorogo, 2024)
The remains of NTT woven fabrics are generally thrown away and not utilized by the community in Kupang Regency. Reusing these remains into various accessories has many uses, which shows that the remains can play a good role if managed in products with a selling value. The purpose of this community service is to improve the skills of pastors in utilizing waste cloth into accessories that have high selling value so that they can pass on this knowledge to the congregation, hoping to improve the economy of the community in Kupang Regency. This service method uses community-based research (CBR) by the service team and partners. The team carried out PKM activities according to the predetermined schedule: August 31 - September 1, 2023. The results of community service activities obtained through activity utilization sheets by distributing questionnaires containing 14 statements to 15 participants showed that 13 participants stated that they were very satisfied with this activity, 86.7%, and two other participants chose the satisfied category with a percentage of 13.3%. This activity is considered very beneficial for pastors in the East Kupang Classis. It is hoped that there will be more in-depth training related to making earrings with the latest models and characteristics so that they can be registered with HKI and need to be continued with business management training.